Brazilian football: between the real and the imaginary - Kupper, Agnaldo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2022)
From the popularization/democratization of football in Brazil, the practice created crusts in the daily life and in the Brazilian imagination, starting to function as a regulatory mechanism of social life. The communication vehicles started to collaborate for the diffusion of ideas and legitimation of speeches in favor of football, corroborating with political and media interests.
Keywords: Football; Imaginary; Press; Spectacularization